PERILAKU PENGGUNAAN IKLAN FACEBOOK TERHADAP KINERJA BISNIS UMKM BERBASIS DIGITAL - Tarigan, Imanuel; Sihotang, Helena; Subiantoro, Nur; Harsono4, Subambang (Jurnal Manajemen dan Bisnis, 2024)
This research investigates the factors that encourage MSMEs to use Facebook advertising and its impact on business kinerjance. Using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), the study validates a theoretical model through a survey of 250 Indonesian MSME owners. The results show a direct and significant influence between compatibility, social influence, and perceived ease of use on Facebook advertising behavior. However, no influence was found from cost, facilitating conditions, or perceived usefulness. The perceived financial resource availability factor has a significant moderating effect on the relationship between Facebook advertising and business kinerjance. Generally, Facebook advertising does not significantly influence business kinerjance, especially in terms of profit and efficiency, but it positively affects indicators supporting business kinerjance, such as growth, personal goals, and reputation.